(untitled) (Salud, Arte y Cuidado, 2025)
The purpose of this study is to analyze the effects produced in the preterm newborn before and after the noise generated in the neonatal intensive care unit of the Pediatric Hospital. Regarding the research methodology, it presents a quantitative approach, field design, non-experimental of a cross-sectional type, the population was taken as 04 preterm newborns admitted to the pediatric and neonatal intensive care unit. To this population, with prior informed consent from the parents, an assessment was applied for Activities that generate noise; includes noise levels, effects that they produce before and after they are generated. Results: The alarm of the monitors, conversation service door, wall aspiration system, care provided to the baby, closing of windows, incubator alarm produced an increase in heart rate, beats per minute and changes in oxygen saturation. It is concluded that the environmental noise of the neonatal intensive care unit exceeds the sound limits considered appropriate for the hospital environment, reaching twice the noise levels considered tolerable for the human ear.